Acute brain injury following illicit drug abuse in adolescent and young adult patients: spectrum of neuroimaging findings. Issue 2 (April 2017) - Shrot, Shai; Poretti, Andrea; Tucker, Elizabeth W; Soares, Bruno P; Huisman, Thierry AGM
The use of illicit drugs is currently a major medical problem among adolescents. Several illicit drugs have a high abuse potential and can be neurotoxic causing high morbidity and mortality. The clinical manifestation of adolescents with acute drug-induced neurotoxicity is often characterized by non-specific symptoms and findings. Early diagnosis is important to prevent death and permanent long-term neurological impairments. We report on clinical and neuroimaging findings in five adolescents with acute brain imaging following illicit drug intoxication to highlight the role of neuroimaging findings in the diagnostic work-up of pediatric acute drug-induced neurotoxicity. Our patients reveal two main neuroimaging patterns of brain injury: diffuse symmetric subcortical white matter injury with preferential cerebellar involvement (leukoencephalopathy pattern) or multiple foci of ischemic infarctions in a non-arterial territory distribution (ischemic pattern). Familiarity with these two neuroimaging patterns of findings in the evaluation of magnetic resonance imaging studies in adolescents with acutely altered mental status may suggest the correct diagnosis, narrow the differential diagnosis, and consequently allow early initiation of targeted laboratory investigations and treatment, potentially improving outcome.